Failure Analysis and Improvement of the Bearing in Gearbox - Yang Zhongchun; Luo Yuan (Jixie chuandong)
The rational allocation of gearbox bearing not only affects the internal structure and the service life,but also determines the service life of the bearing itself.Combining with the Xiangtan Iron and steel wire 12 Vgearbox bearing,the site analysis is performed,the improved optimization scheme and implement are proposed,agood effect is obtained.